?-Ketoglutarate couples cellular metabolism to developmental growth via hydroxylation-dependent degradation of Yorkie. - He, T.; Zeng, Y.; Zhou, J.; Tian, Y.; Wang, D.; Ma, J.; Liu, J.; Wu, W.; Wei, C.; Jiao, R. (Cell reports, 2026)
The evolutionarily conserved Hippo signaling pathway, essential for development and tissue homeostasis, is intimately linked to cellular metabolism. While cellular ?-ketoglutarate (?-KG) levels fluctuate with metabolic state, the functional significance of these fluctuations for development remains poorly defined. Here, this study uncovers an evolutionarily conserved mechanism whereby ?-KG directly regulates Hippo signaling activity during development. We demonstrate that elevated ?-KG promotes the degradation of Yki, the key Hippo pathway effector in Drosophila, in a concentration-dependent manner. Mechanistically, ?-KG drives PH4?EFB-mediated prolyl hydroxylation of specific proline residues in Yki, thereby targeting it for ubiquitination and proteasomal degradation. Critically, mutation of these hydroxylation sites of Yki abolishes its sensitivity to ?-KG, resulting in Yki protein hyperstabilization, aberrant activation of Hippo targets, and organ overgrowth in Drosophila. Overall, these findings establish ?-KG as a central metabolic regulator of Hippo activity, thereby coupling metabolic status to developmental growth control.